Comparative Analysis of Financial Performance of Asset Portfolios between Islamic Banks and Conventional Banks in Indonesia - Refa Gustia; Didi Ashari; Peny Cahaya Azwari; Ayke Nuraliati (Jurnal Akuntansi dan Keuangan, 2025)
AbstracThis study aims to compare the financial performance between Islamic banks and conventional banks in Indonesia using key financial ratios such as Return on Assets (ROA), Return on Equity (ROE), Non-Performing Loan (NPL), and Non-Performing Financing (NPF). The objects of this study are Bank Syariah Indonesia (BSI) as the representative of Islamic banks, and Bank Central Asia (BCA) as the representative of conventional banks. The data used are derived from the annual financial statements of both banks over a certain period. The results of the study show that although BCA, as a conventional bank, tends to have larger assets and higher profitability, BSI demonstrates better financial stability, reflected by a lower NPF ratio. This indicates that Islamic banks, with a focus on asset-based financing, have more cautious risk management and are better able to manage financing risks effectively. In contrast, BCA, as a conventional bank, is more vulnerable to interest rate fluctuations, as evidenced by a relatively higher NPL ratio. This study is expected to provide insights for regulators, academics, and banking practitioners in formulating policies to enhance the performance and stability of the banking sector in Indonesia.Keywords: Islamic Banks, Conventional Banks, Indonesian Banking Sector